2015
DOI: 10.1002/oby.21316
|View full text |Cite
|
Sign up to set email alerts
|

The efficacy of sugar labeling formats: Implications for labeling policy

Abstract: Objective: To examine knowledge of sugar recommendations and test the efficacy of formats for labeling total and added sugar on pre-packaged foods. Methods: Online surveys were conducted among 2008 Canadians aged 16-24. Participants were asked to identify recommended limits for total and added sugar consumption. In Experiment 1, participants were randomized to one of six labeling conditions with varying information for total sugar for a high-or low-sugar product and were asked to identify the relative amount o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
29
0
4

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(34 citation statements)
references
References 24 publications
(26 reference statements)
1
29
0
4
Order By: Relevance
“…39 Furthermore, around one-quarter of Canadians aged 16-24 years cannot identify whether there is added sugar present in a food item when there is no information about added sugar on the nutrition facts table. 40 In an effort to address the confusion over added sugars, the US has recently finalized updates to their nutrition facts label that include requirements to distinguish between intrinsic and added sugars, with a percent daily value for added sugars based on the US Department of Agriculture recommendation that they not exceed 10% of total daily calories. 41 Health Canada has also recently considered the addition of an added sugar value on nutrition facts tables as well as a reorganization of the ingredients list that would group all sugars together in a set of brackets, which may aid consumers in finding and reading added sugars in the list of ingredients.…”
Section: Discussionmentioning
confidence: 99%
“…39 Furthermore, around one-quarter of Canadians aged 16-24 years cannot identify whether there is added sugar present in a food item when there is no information about added sugar on the nutrition facts table. 40 In an effort to address the confusion over added sugars, the US has recently finalized updates to their nutrition facts label that include requirements to distinguish between intrinsic and added sugars, with a percent daily value for added sugars based on the US Department of Agriculture recommendation that they not exceed 10% of total daily calories. 41 Health Canada has also recently considered the addition of an added sugar value on nutrition facts tables as well as a reorganization of the ingredients list that would group all sugars together in a set of brackets, which may aid consumers in finding and reading added sugars in the list of ingredients.…”
Section: Discussionmentioning
confidence: 99%
“…One of the challenges for Nutritional Scientists in communicating to an often confused public [33] , in the face of changing guidelines, is the terminology used to describe dietary sugars (Table 2); and the adoption of the WHO term 'free sugars' by the UK ,replacing the previous 'nonmilk extrinsic sugars', is considered beneficial [36] . The terms 'free sugars' [4,5] and 'added sugars' [6][7][8] are essentially equivalent in describing sugars (mono-and disaccharides) added to foods and beverages by the manufacturer, cook or consumer, and sugars found in honey, syrups, fruit juices and juice concentrates ( Table 2).…”
Section: Hidden Dietary Sugars and The Challenge For Public Healthmentioning
confidence: 99%
“…Most US adults report consuming more added sugar than recommended for a healthy diet and are seeking ways to cut back. The data published here by Vanderlee et al suggest that the FDA proposal to include added sugar and a %DV on Nutrition Facts labeling will likely be helpful to consumers.…”
mentioning
confidence: 80%
“…In two simple, important, and timely experiments, Vanderlee et al have demonstrated that information on added sugar proposed for inclusion on Nutrition Facts labels will be helpful to consumers. The US Food and Drug Administration (FDA) has proposed requiring on Nutrition Facts labels that added sugar be disclosed and that the label include a percent daily value (%DV), based upon the report of the 2015 Dietary Guidelines Advisory Committee (DGAC) .…”
mentioning
confidence: 99%